Numerical analysis of evaporation reduction in floating photovoltaic power plants: influence of design parameters - Berlioux Baptiste; Amiot Baptiste; Ferrand Martin; Le Berre Rémi; Rhazi Oume-Lgheit; Vidal Javier; Pabiou Hervé; Knikker Ronnie (EPJ Photovoltaics)
Evaporation reduction is one of the advantages provided by floating photovoltaic (FPV) power plants. However, few studies have yet been carried out to understand how to optimise the layout of FPV power plants in order to provide better water management. Indeed, the interaction between atmospheric conditions, water bodies, and the FPV plant creates a dynamic system that is challenging to study and accurately model. This paper investigates the impact on evaporation of various characteristics of FPV plants, such as float technology, plant positioning and orientation, distribution, and coverage ratio. This study was performed using Computational Fluid Dynamics (CFD) of the surrounding atmosphere, with the impact of the FPV plant modelled using specific boundary conditions to reduce computational costs. The numerical results show that the coverage ratio is the most important factor in reducing evaporation. Full coverage could reduce evaporation by 52.8% for a plant with a large footprint on the water and by 43.4% for a plant with a smaller footprint. Other parameters have only a moderate impact, allowing the fine-tuning of evaporation reduction. The optimal configuration would involve covering the entire water body with a single large water footprint island positioned downwind of the prevailing transversal winds. This setup significantly reduces evaporation, thereby enhancing water conservation and making an FPV power plant a valuable tool in sustainable water management.